Impact of Infectious Disease Consultation in Patients With Candidemia: A Retrospective Study, Systematic Literature Review, and Meta-analysis. (3rd August 2020) - Kobayashi, Takaaki; Marra, Alexandre R; Schweizer, Marin L; Ten Eyck, Patrick; Wu, Chaorong; Alzunitan, Mohammed; Salinas, Jorge L; Siegel, Marc; Farmakiotis, Dimitrios; Auwaerter, Paul G; Healy, Heather S; Diekema, Daniel J
Abstract: Background: Morbidity and mortality from candidemia remain unacceptably high. While infectious disease consultation (IDC) is known to lower the mortality from Staphylococcus aureus bacteremia, little is known about the impact of IDC in candidemia. Methods: We conducted a retrospective observational cohort study of candidemia patients at a large tertiary care hospital between 2015 and 2019. The crude mortality rate was compared between those with IDC and without IDC. Then, we systematically searched 5 databases through February 2020 and performed a meta-analysis of the impact of IDC on the mortality of patients with candidemia. Results: A total of 151 patients met the inclusion criteria, 129 (85%) of whom received IDC. Thirty-day and 90-day mortality rates were significantly lower in the IDC group (18% vs 50%; P = .002; 23% vs 50%; P = .0022, respectively). A systematic literature review returned 216 reports, of which 13 studies including the present report fulfilled the inclusion criteria. Among the 13 studies with a total of 3582 patients, IDC was performed in 50% of patients. Overall mortality was 38.2% with a significant difference in favor of the IDC group (28.4% vs 47.6%), with a pooled relative risk of 0.41 (95% CI, 0.35–0.49). Ophthalmology referral, echocardiogram, and central line removal were performed more frequently among patients receiving IDC. Conclusions: This study is the first systematic literature review and meta-analysis to evaluate the association between IDC and candidemia mortality. IDC was associated with significantly lower mortality and should be considered in all patients with candidemia.